Double Helix Jeopardy. - Cole, S.A (IEEE spectrum)
DNA database help solve crimes but aid and abet racial discrimination. An arrest-only database would have the look and feel of a universal DNA database for black males. Although the DNA-database debate will probably occupy judges, legal scholars, and legislators for some time, the most likely outcome is the least equitable-including only arrestees. Indeed, if policy-makers were purposefully trying to find the most discriminatory system possible, an arrestee database would be the ideal choice.